Antioxidant Activity and Thermal Stability of Oleuropein and Related Phenolic Compounds of Olive Leaf Extract after Separation and Concentration by Salting-Out-Assisted Cloud Point Extraction - Konstantinos Stamatopoulos; Evangelos Katsoyannos; Arhontoula Chatzilazarou (MDPI AG, 2014)
A fast, clean, energy-saving, non-toxic method for the stabilization of the antioxidant activity and the improvement of the thermal stability of oleuropein and related phenolic compounds separated from olive leaf extract via salting-out-assisted cloud point extraction (CPE) was developed using Tween 80. The process was based on the decrease of the solubility of polyphenols and the lowering of the cloud point temperature of Tween 80 due to the presence of elevated amounts of sulfates (salting-out) and the separation from the bulk solution with centrifugation. The optimum conditions were chosen based on polyphenols recovery (%), phase volume ratio (Vs/Vw) and concentration factor (Fc). The maximum recovery of polyphenols was in total 95.9%; Vs/Vw was 0.075 and Fc was 15 at the following conditions: pH 2.6, ambient temperature (25 °C), 4% Tween 80 (w/v), 35% Na2SO4 (w/v) and a settling time of 5 min. The total recovery of oleuropein, hydroxytyrosol, luteolin-7-O-glucoside, verbascoside and apigenin-7-O-glucoside, at optimum conditions, was 99.8%, 93.0%, 87.6%, 99.3% and 100.0%, respectively. Polyphenolic compounds entrapped in the surfactant-rich phase (Vs) showed higher thermal stability (activation energy (Ea) 23.8 kJ/mol) compared to non-entrapped ones (Ea 76.5 kJ/mol). The antioxidant activity of separated polyphenols remained unaffected as determined by the 1,1-diphenyl-2-picrylhydrazyl method.